Accounting for Affirmative Action Programs: A Stochastic Flow Approach. - Churchill, Neil C.; Shank, John K. (The Accounting Review, 1975)
This article presents an analytic model of the "management succession" process which can be used to plan, control and account for an organization's affirmative action programs. The authors describe a field study of the management succession process in a large corporation and the development of a formal stochastic model based on the empirical findings. They then illustrate how that model can be used in conjunction with an interactive computer program to help evaluate the company's affirmative action plans and to monitor the success of the programs designed to achieve them. The field-based research project was initiated with four main objectives. The first was to determine if a flow analysis in the form of matrices of employee transition probabilities could be developed for an actual corporation. The second objective was to see if data presented in the form of transition or flow matrices provide useful information. The third objective was to ascertain if such information would possess the properties necessary for the development of a formal stochastic model of the process for use in management analysis, planning and control. Fourth, if such a model could be developed, the authors wanted to see how it might be of use to management.